In Solving Refugee Issues Solidarity Must Come First - Susan McMonagle (Policy and Practice: A Development Education Review, 2017)
With the number of people displaced globally at record levels, effective solutions to refugee issues – both for refugees and the communities that host them – are vital. A ‘business as usual approach’ will no longer suffice. Instead, collaborative solutions that ensure responsibility sharing and recognise the connection between displacement and development should be the way forward. The international community has made some strides in recognising this. With the adoption of the 2030 Agenda on Sustainable Development and the New York Declaration in September 2016, world leaders have agreed that refugees must be factored into all development plans. Solidarity with refugees and host states must be prioritised.